On the role of vertical differentiation in enhancing the survival of export flows: Evidence from a developing country - Kemal Türkcan; Hülya Saygili (Kiel Institute for the World Economy (IfW), 2017)
This paper analyzes the role of vertical differentiation linked with global production networks in increasing the chance of export survival using highly disaggregated machinery exports data from Turkey for the 1998-2013 period. Results obtained from the descriptive statistics analysis suggest that the duration of Turkey's machinery exports is remarkably short with a median duration of merely one year. In addition, the likelihood of the survival of exports varies widely across total machinery, finished and parts and components as well as across trade types (horizontally and vertically differentiated products). Based on discrete-time duration models, the empirical results demonstrate that vertical differentiation together with product and market diversification are associated with a higher export survival rate, particularly for parts and components. The evidence hence supports the hypothesis that global production sharing activities greatly increase the chances of survival in export markets.
Keywords: F10; F14; C41; 330; export duration; survival analysis; vertical differentiation; global production networks